The 30-day outcome of neonates operated for esophageal atresia - Corné de Vos; L van Wyk; D Sidler; P Goussard (EL-Med-Pub, 2022)
Background: Despite great advances in the overall management of neonates with esophageal atresia (EA), many complications leading to morbidity still occurs.  Most complications can be treated conservatively, but effective management is needed to reduce long-term morbidity.  Methods: A retrospective cohort study was performed on neonates treated for EA with/without a tracheoesophageal fistula (TEF) between 2001 and 2020.  Data were collected from patient records, discharge summaries, and surgical notes.  The information recorded included: maternal and neonatal demographics, information regarding the diagnosis, and details surrounding the surgery. Results: During the 19-year study period, 53 neonates with a mean gestational age of 36.7 weeks were included for analysis.  Forty-nine percent presented with an associated anomaly (most commonly, complex cardiac lesions).  The majority (83%) had a primary repair on a median of day 3 of life.  Nineteen neonates had a surgical complication 30 days post-repair: 7 minor (contained leaks and a chylothorax) and 12 major complications including anastomotic strictures, major anastomotic breakdowns, a recurrent TEF, and 5 surgery-related mortalities. Conclusions: This study showed less morbidity and mortality of neonates born with EA, despite a high incidence of associated anomalies, in a resource-restricted hospital.  It is important to highlight that even with limited resources, centers in low- or middle-income countries can have good outcomes.